The role of foreign special libraries and information centers in the Philippines - Balarao, Vanessa G. (2003)
International library movement is the name given to the establishments of libraries worldwide (Johan Van Halm, 1978). The Foreign special libraries and information centers in the Philippines vary when it comes to services. They are here to disseminate relevant and up-to-date materials in fields of research and development. The services depend on the specialized subject. They also have other activities besides from their usual function of disseminating information. The activities come in different ways like seminars, concerts and outreach programs.